HUBUNGAN CITRA TUBUH DAN HARGA DIRI DENGAN PERILAKU SEKSUAL PRANIKAH PADA SISWA SMA SWASTA DI JAKARTA PUSAT - Jolene Budiono; Francisca Tjhay; Surilena Surilena; Bryany Titi Santi; Isadora Gracia (JURNAL KESEHATAN REPRODUKSI, 2024)
The Relationship Between Body Image and Self-Esteem and Premarital Sexual Behavior among High School Students in Central Jakarta Background: The prevalence of sexual activity among adolescents is on the rise as they embark on dating and prepare for marriage. Typically, premarital sexual behavior initiates in adolescence and can be influenced by factors such as body image and self-esteem. Objective: This study aims to explore the relationship between body image, self-esteem, and premarital sexual behavior among high school students in Central Jakarta. Method: The study was a cross-sectional and conducted on 449 students in Central Jakarta. The measuring instruments used were Characteristic, Sexual Behavior, Multidimensional Body Self-Relations Questionnaire-Appearance Scale, and Rosenberg Self-Esteem Scale questionnaires. Data analyzed using univariate and bivariate tests. Result: There are 39% low body image, 61.7% low self-esteem, 54.8% less safe risky sexual behavior and 10.2% are unsafe risky sexual behavior, 46% girls and 31.2% boys with low self-esteem, 66% boys and 43.9% girls with less safe risk behavior. Meanwhile 12.7% boys and 7.9% girls with unsafe risk behavior. Bivariate analysis shows that there is no relationship between body image, self-esteem, and premarital sexual behavior in high school students. Conclusion: There is no significant relationship between body image and self-esteem and premarital sexual behavior in private high school students in Central Jakarta.  However, the risk of sexual behavior is high.